Analysis of Financial Performance on Company Value with Financial Health as an Intervening Variable - Diraningsurya, Ica Oktavia; Triyono, Triyono (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of financial performance with profitability ratio, leverage, and activity on company value with financial health as an intervening variable in manufacturing companies on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique in this study was purposive sampling. The data analysis method in this study applied multiple linear regression analysis, path test, and Sobel test with the help of SPSS software version 30 and Sobel Test Calculation for the Significance of Mediation. The number of companies that meet the criteria is 162 companies with 486 data samples, and outlier handling is carried out on 421 data samples. The results of the study indicate that profitability, leverage, and activity have a significant effect on financial health. Profitability, leverage, and financial health have a significant effect on firm value, while activity has no effect. In addition, financial health mediates the relationship between leverage and firm value, but does not mediate the relationship between profitability or activity and firm value.